Ferrovia sorocabana: proposta de reativação do trecho entre os municípios de Presidente Prudente e Presidente Epitácio - Sampaio, Carlos Eduardo de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The first railroads in Brazil appeared between mid and late nineteenth century. In 1858 came the Dom Pedro II Railway in Rio de Janeiro and, in 1867, the São Paulo Railway Railway, in English capital, in São Paulo. With the development of the coffee culture the Railway Companies were created, among them the Sorocabana Railroad (1876). Over the years, the Sorocabana Railroad has expanded throughout much of the interior of São Paulo, boosting population growth in several cities in the State of São Paulo and even the founding of some municipalities. In the 1920s, Sorocabana reached the city of Presidente Epitácio, a border with the state of Mato Grosso (now Mato Grosso do Sul), also reaching the border with the State of Paraná. It is important to remember that the Sorocabana railroad was extremely important for the transportation of cargo and passengers in the state of São Paulo. In the 1990s, with the adherence to neoliberal policies, the process of privatization of the federal railroads (RFFSA - Ferrocarril Federal SA, FERRONORTE, Norte Sul and others) and state (FEPASA - Ferrovia Paulista S / A and FERROPAR - Ferrovia Paraná S / A), granted to private companies. The Sorocabana Railroad was granted to América Latina Logística and in the early 2000s the stretch between Presidente Prudente-Presidente Epitácio was deactivated. This monograph aims to understand the importance of the rail system for integration in the region of Presidente Prudente, with the Sorocabana Railroad in the section between Presidente Prudente and Presidente Epitácio. The methodology was based on the following activities: bibliographic review, site surveys, visits to the Sorocaba Railway Museum in the city of Sorocaba / SP...

As primeiras ferrovias no Brasil surgiram entre meados e final do século XIX. Em 1858 surgiu a Estrada de Ferro Dom Pedro II, no Rio de Janeiro e, em 1867, a Estrada de Ferro São Paulo Railway, de capital inglês, em São Paulo. Com o desenvolvimento da cultura do café foram criadas as Companhias Ferroviárias, entre elas a Estrada de Ferro Sorocabana (1876). Ao longo dos anos, a Estrada de Ferro Sorocabana expandiu-se por grande parte do interior paulista, impulsionando o crescimento populacional em diversas cidades do Estado de São Paulo e, até mesmo, a fundação de alguns municípios. Na década de 1920, a Sorocabana atinge a cidade de Presidente Epitácio, divisa com o estado do Mato Grosso (atual Mato Grosso do Sul), chegando também à divisa com o Estado do Paraná. É importante lembrar que a ferrovia Sorocabana foi de extrema importância para o transporte de cargas e de passageiros no estado de São Paulo. Nos anos 1990, com a adesão às políticas neoliberais, inicia-se, sobretudo a partir de 1995 o processo de desestatizações das ferrovias federais (RFFSA - Rede Ferroviária Federal S.A, FERRONORTE, Norte Sul e outras) e estaduais (FEPASA - Ferrovia Paulista S/A e FERROPAR - Ferrovia Paraná S/A), concedidas às empresas privadas. A Ferrovia Sorocabana foi concedida à América Latina Logística e no início dos anos 2000 o trecho entre Presidente Prudente-Presidente Epitácio foi desativado. Esta monografia objetiva-se compreender a importância do sistema ferroviário para a integração na região de Presidente Prudente, com destaque a Ferrovia Sorocabana no trecho entre Presidente Prudente - Presidente Epitácio. A metodologia baseou-se na realização das seguintes atividades: revisão bibliográfica, pesquisas em sites, visita ao Museu da Estrada de Ferro Sorocabana no município de Sorocaba/SP...
Keywords: Geografia; Trens de ferro; Ferrovias - Presidente Epitácio (SP); Ferrovias - Presidente Prudente (SP); Geography